Acute Thyroiditis and Bilateral Optic Neuritis following SARS-CoV-2 Vaccination with CoronaVac: A Case Report. (18th August 2021) - Leber, Henrique M.; Sant'Ana, Leticia; Konichi da Silva, Nina R.; Raio, Mariana C.; Mazzeo, Thiago Jose Muniz Machado; Endo, Camila Matsuura; Nascimento, Heloisa; de Souza, Carlos E.
ABSTRACT: Purpose: To describe a case of acute thyroiditis and bilateral optic neuritis associated with SARS-CoV-2 vaccination. Methods: A single case report from a tertiary referral center. Results: The patient described in the following case report developed acute thyroiditis and bilateral optic neuritis following SARS-CoV-2 vaccination. The patient underwent pulse therapy followed by oral tapering corticosteroid therapy with an improvement of the bilateral disc swelling and the visual field, and recovery of thyroid-stimulating hormone to the normal limits. Conclusion: Although the association between immunization and the onset of demyelinating manifestations of the central nervous system is well documented, this is the first reported case of bilateral optic neuritis and acute thyroiditis and subsequent to administration of vaccination against SARS-CoV-2.